Effect of Foliar Application of Plant Growth Regulators on Growth, Flowering and Yield of Tomato (Lycopersicon Esculentum l.) Under Protected Condition - Bhattarai, Basant Raj; Rijal, Louish; Bhattarai, Avash; Khanal, Prabha (Journal of Jayaprithvi Multiple Campus, 2025)
A field experiment was carried out under greenhouse to assess the performance of tomato cv. Srijana as influenced by sole application of GA3 and NAA during the summer season of 2021–2022 at the horticulture farm of the school of agriculture, Tikapur, Kailali, Nepal. The seven different treatments consisted of two plant growth regulators each having three concentrations was used viz., T1 (GA3 @ 25 ppm), T2 (GA3 @ 50 ppm), T3 (GA3 @ 75 ppm), T4 (NAA @ 20 ppm), T5 (NAA @ 40 ppm), T6 (NAA @ 60 ppm) and T7 (Control: water spray). Treatments were replicated thrice in the single factorial randomized complete block design (RCBD). Max/min, temperature/humidity was measured 30 °C/13 °C, 87%/60%. The results revealed that the treatment T1 (GA3 25 ppm) had a significant effect on growth and flowering parameters mainly plant height, leaf length, leaf width, leaf area meter, number of flower clusters per plant, number of clusters per plant, number of flower per cluster, number of fruit per cluster, number of fruit per plant and number of fruit set per plant. Similarly, a significantly higher yield (60.83 ton/ha) of tomato was attained with GA3 @ 25 ppm. It could be suggested that the production of tomatoes could be improved by the sole application of GA3 @ 20 ppm under the controlled condition of Kailali, Nepal.